2022
DOI: 10.1186/s12879-021-07000-y
|View full text |Cite
|
Sign up to set email alerts
|

AmpC hyperproduction in a Cedecea davisae implant-associated bone infection during treatment: a case report and therapeutic implications

Abstract: Background Data on antimicrobial resistance mechanisms are scanty for Cedecea spp., with very variable antibiotic resistance patterns documented. Here we report the first in vivo resistance evolution of a C. davisae clinical isolate in a patient with a complex hand trauma and provide insight in the resistance mechanism, leading to therapeutic implications for this pathogen. Case presentation Cedecea davisae was isolated from a patient with hand tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Clinical strains of Cedecea species exhibit natural resistance to various antimicrobial agents such β-lactams and colistin, which tend to confer the behavior of an emerging opportunistic human pathogen (Thompson and Sharkady 2021). Studies have reported that Cedecea encodes genes for antimicrobial resistance, but the exact proteins encoding such genes are not known (Thompson and Sharkady 2021;Notter et al 2022;Ginn et al 2018) In 2015, a previously undiscovered species from the genus Cedecea, specifically identified as Cedecea neteri SSMD04, was first isolated from pickled mackerel sashimi (Tan et al 2015). C. neteri SSMD04 is a gram-negative, bacillus that is found relatively rare in nature, but was recently identified as the infectious agent of a urinary tract infection in a pregnant female with polyhydramnios (Ahmad et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical strains of Cedecea species exhibit natural resistance to various antimicrobial agents such β-lactams and colistin, which tend to confer the behavior of an emerging opportunistic human pathogen (Thompson and Sharkady 2021). Studies have reported that Cedecea encodes genes for antimicrobial resistance, but the exact proteins encoding such genes are not known (Thompson and Sharkady 2021;Notter et al 2022;Ginn et al 2018) In 2015, a previously undiscovered species from the genus Cedecea, specifically identified as Cedecea neteri SSMD04, was first isolated from pickled mackerel sashimi (Tan et al 2015). C. neteri SSMD04 is a gram-negative, bacillus that is found relatively rare in nature, but was recently identified as the infectious agent of a urinary tract infection in a pregnant female with polyhydramnios (Ahmad et al 2021).…”
Section: Introductionmentioning
confidence: 99%